2020
DOI: 10.1016/j.cels.2020.03.003
|View full text |Cite|
|
Sign up to set email alerts
|

BraInMap Elucidates the Macromolecular Connectivity Landscape of Mammalian Brain

Abstract: Highlights d BraInMap is a global proteomic survey of over 1,000 multiprotein brain complexes d Near-native complex identification by CF-MS and reconstruction by computer learning d Technique interrogates complexes in normal and pathophysiological context d Allows study of functional modules that are adversely affected in neurological diseases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 111 publications
0
51
0
Order By: Relevance
“…Within this family, IgLON sub-family members include Negr1 (also known as Kilon), Lsamp, OPCML, and neurotrimin; these highly glycosylated proteins display three immunoglobulin domains and are anchored to the cell membrane by a glycosylphosphatidylinositol motif inserted in their C termini [16]. Lsamp direct interaction with Negr1 has been previously observed in protein microarray experiments [17] and recently confirmed in mouse brain [18]. Lsamp function in serotonergic signalling has been suggested by the findings that Lsamp -/mice showed lower 5-HT levels and higher 5-HT turnover, which have been called to explain their low anxiety and aggression [19,20].…”
Section: Introductionmentioning
confidence: 85%
“…Within this family, IgLON sub-family members include Negr1 (also known as Kilon), Lsamp, OPCML, and neurotrimin; these highly glycosylated proteins display three immunoglobulin domains and are anchored to the cell membrane by a glycosylphosphatidylinositol motif inserted in their C termini [16]. Lsamp direct interaction with Negr1 has been previously observed in protein microarray experiments [17] and recently confirmed in mouse brain [18]. Lsamp function in serotonergic signalling has been suggested by the findings that Lsamp -/mice showed lower 5-HT levels and higher 5-HT turnover, which have been called to explain their low anxiety and aggression [19,20].…”
Section: Introductionmentioning
confidence: 85%
“…Recent proteomic studies identified proteins associated with M6a that participate in neurite outgrowth and axon elongation ( Figures 1B,C ; Sato et al, 2011a ; Huttlin et al, 2017 ; Aparicio et al, 2020 ; Haenig et al, 2020 ; Pourhaghighi et al, 2020 ). To emphasize some examples, we divided them into 3 groups: (i) Cytoplasmic proteins: which include cytoskeleton adaptor molecules and cytoskeleton organization pathways which might interact with M6a’s cytoplasmic tails as Ras kinases 2, DiRas2 ( Grunewald et al, 2021 ) and the kinases mentioned above.…”
Section: M6a and Synapse Formationmentioning
confidence: 99%
“…This subject exceeds the topics covered in this review, and no functional experiments were reported yet, but we would like to highlight a few insights. Pourhaghighi et al (2020) identified associated protein complexes in adult mammal brains and built BraInMap 2 . M6a was found within a complex of 30 interacting proteins, some of which are myelin sheath proteins, including the main myelin glycoproteins PLP and MAG; or are myelin sheath associated proteins like contactin 1 and contactin associated protein 1.…”
Section: M6a’s Potential Role In Neuron-glia Interactionmentioning
confidence: 99%
“…The laboratory mouse, Mus musculus, is possibly the most important model species that has been used extensively in the study of genetics [299]. Due to its importance to the understanding of human disease, the mouse interactome has been a key research goal since completion of the mouse genome, and a wealth of experimental [89,[300][301][302][303][304][305][306][307][308] and computational [13,64,188,198,[309][310][311][312] interactome data have been produced, which along with human and yeast data, form the basis of interactome studies in many other mammals (Table 6). One of the largest, MouseNet, represents a large-scale PFIN produced via machine learning based on multiple types of functional interaction data including PPIs, expression and phenotypes.…”
Section: Mammalsmentioning
confidence: 99%